The Choice of the Appropriate Technology Assumption for Calculating Symmetric Product-by-Product Input-Output Table with Reference to Four Desirable Properties Introduced by Jansen and ten Raa - Parisa Mohajeri; Zahra Zabihi; Sahar Sadeghi; Ziba Eghtesadi (فصلنامه پژوهش‌های اقتصادی ایران, 2016)
Since the introduction of supply-use input-output model by the United Nations in its 1968 SNA, there has been a controversy on choosing the most appropriate technology assumption for estimating symmetric product by product input-output table. These arguments have focused on two technology assumptions; the product technology assumption (PTA) and the activity technology assumption (ATA). The PTA states that each product has a unique input structure that is independent of producing industry. In contrast, the ATA is defined as each activity has its own specific way of production, irrespective of its product mix. Each assumption has its own advantages and disadvantages. Because of ATA’s inconsistency with some fundamental economic theories, “Product Technology” assumption is more widely applied for calculating symmetric product-by-product input-output table. In this paper, we show that only PTA fulfills the four desirable properties (material balance, financial balance, scale invariance and price invariance) which are introduced by Jansen and ten Raa (1990) but ATA fulfils only one of them. This result can be used by compliers and users in choosing the appropriate economic assumptions for deriving symmetric input-output tables.